2021
DOI: 10.1021/acs.jpcb.1c00885
|View full text |Cite
|
Sign up to set email alerts
|

Glassy and Polymer Dynamics of Elastomers by 1H-Field-Cycling NMR Relaxometry: Effects of Fillers

Abstract: 1 H spin–lattice relaxation rate ( R 1 ) dispersions were acquired by field-cycling (FC) NMR relaxometry between 0.01 and 35 MHz over a wide temperature range on polyisoprene rubber (IR), either unfilled or filled with different amounts of carbon black, silica, or a combination of both, and sulfur cured. By exploiting the frequency–temperature superposition principle and constructing master curves for the total FC NMR susceptibility, χ″(ω) = ω R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 94 publications
(191 reference statements)
0
5
0
Order By: Relevance
“…Therefore, FC NMR has proven to be an effective technique to characterize the dynamics of polymers far above glass transition over a broad range of characteristic motion times [47,48]. In particular, it has been successfully applied to obtain information on segmental and polymer dynamics in polymer melts and vulcanized rubbers [49][50][51][52][53][54]. For this aim, R 1 (ω) data are usually transformed to the susceptibility representation, χ"(ω) = ω R 1 (ω), and χ"(ωτ s ) master curves are built from χ"(ω) curves acquired at different temperatures by exploiting the frequency-temperature superposition (FTS) principle [55,56] to determine the values of the correlation time for segmental dynamics, τ s .…”
Section: Characterization Of Dynamicsmentioning
confidence: 99%
“…Therefore, FC NMR has proven to be an effective technique to characterize the dynamics of polymers far above glass transition over a broad range of characteristic motion times [47,48]. In particular, it has been successfully applied to obtain information on segmental and polymer dynamics in polymer melts and vulcanized rubbers [49][50][51][52][53][54]. For this aim, R 1 (ω) data are usually transformed to the susceptibility representation, χ"(ω) = ω R 1 (ω), and χ"(ωτ s ) master curves are built from χ"(ω) curves acquired at different temperatures by exploiting the frequency-temperature superposition (FTS) principle [55,56] to determine the values of the correlation time for segmental dynamics, τ s .…”
Section: Characterization Of Dynamicsmentioning
confidence: 99%
“…31 The presence of a mineral filler dispersed into the rubber matrix and its influence on the nucleation phase of temperature-induced crystallization is still unclear. Even though it is reported that filler particles affect polymer chain conformations and local reptation, 32 the effect they have on nucleation is argued to be negative by some authors, 33 since fillers create a region with hindered mobility where the nucleation and crystallite growth are slowed down; neutral by others, 34 claiming that fillers extensively affect only the crosslinking reaction, not the crystallization; and positive by some, 35 that suggest fillers favor the formation of nuclei via polymer chain adsorption, interaction, or even confinement of macromolecules inside a filler network.…”
Section: Crystallization and Melting Behaviormentioning
confidence: 99%
“…Solid-state nuclear magnetic resonance (SSNMR) has established itself as one of the most powerful techniques for the characterization of polymer structure and dynamics [36][37][38]. In the case of elastomeric materials, 1 H spin-lattice (T 1 , T 1ρ ), spin-spin (T 2 ) relaxation times, and residual 1 H-1 H dipolar couplings have proved to be valuable tools to disclose the effects of different formulations and vulcanization conditions on the structural and dynamic properties of the polymer network [39][40][41][42][43][44]. In a recent work by some of the authors, SSNMR was employed to study styrene-butadiene rubber (SBR) compounds of technological interest for the tire industry, before and after the addition of the petroleumderived tackifying resin Kristalex™ 5140 [44].…”
Section: Introductionmentioning
confidence: 99%